Management of advanced heart failure: a review. (2nd November 2018) - Kalmanovich, Eran; Audurier, Yohan; Akodad, Mariama; Mourad, Marc; Battistella, Pascal; Agullo, Audrey; Gaudard, Philippe; Colson, Pascal; Rouviere, Philippe; Albat, Bernard; Ricci, Jean-Etienne; Roubille, François
ABSTRACT: Introduction : Heart failure (HF) has become a global pandemic. Despite recent developments in both medical and device treatments, HF incidences continues to increase. The current definition of HF restricts itself to stages at which clinical symptoms are apparent. In advanced heart failure (AdHF), it is universally accepted that all patients are refractory to traditional therapies. As the number of HF patients increase, so does the need for additional treatments, with an increased proportion of patients requiring advanced therapies. Areas covered : This review discusses extensive evidence for the effect of medical treatment on HF, although the data on the effect on AdHF is scare. Authors review the relevant literature for treating AdHF patients. Furthermore, mechanical circulatory devices (MCD) have emerged as an alternative to heart transplantation and have been shown to enhance quality of life and reduce mortality therefore authors also review the current literature on the different MCD and technologies. Expert commentary : More patients will need advanced therapies, as the access to heart transplantation is limited by the number of available donors. AdHF patients should be identified timely since the window of opportunities for advanced therapy is narrow as their morbidity is progressive and survival is often short.